The perception of safety climate towards safety attitude among employees in Jabatan Kerja Raya / Nur Anis Abdul Aziz - Abdul Aziz, Nur Anis (2017)
Safety climate can be described as individual perceptions and understanding towards the value of safety in the work environment. In an organization, safety climate refers to employees’ though about the organization movement on the safety in their workplace and towards the Occupational Safety and Health (OSH) issues. In Jabatan Kerja Raya Pulau Pinang, safety had became on of the main issues that influences the employees and surrounding of their workplace. A research has been done on The Perception of Safety Climate towards Safety Attitudes among Employees in Jabatan Kerja Raya Pulau Pinang. Thus, 60 employees has been selected to answer the questionnaire. SPSS has been used to analysed the data that has been received from the questionnaire. From the results, there are two hypothesis that has been accepted and another two hypothesis has been rejected.